2018
DOI: 10.1155/2018/8198365
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Mediated Regulation of Schwann Cell Migration and Proliferation in Peripheral Nerve Injury

Abstract: Schwann cells (SCs) contribute to nerve repair following injury; however, the underlying molecular mechanism is poorly understood. MicroRNAs (miRNAs), which are short noncoding RNAs, have been shown to play a role in neuronal disease. In this work, we show that miRNAs regulate the peripheral nerve system by modulating the migration and proliferation of SCs. Thus, miRNAs expressed in peripheral nerves may provide a potential therapeutic target for peripheral nerve injury or repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a group of evolutionary conserved small noncoding RNAs that exist in the form of RNA double transcripts of about 22 nucleotides . The miRNA lin‐4 in C. elegans was first discovered in 1993, and since then a large number of miRNAs have been detected in a variety of animals, plants, bacteria, and even viruses .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of evolutionary conserved small noncoding RNAs that exist in the form of RNA double transcripts of about 22 nucleotides . The miRNA lin‐4 in C. elegans was first discovered in 1993, and since then a large number of miRNAs have been detected in a variety of animals, plants, bacteria, and even viruses .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs play a wide range of roles in regulating life activities through posttranscriptional inhibition. MiRNAs are involved in multiple biological processes including cell proliferation, differentiation, and metabolism [13, 19, 29] by modulating specific genes. It has been shown that miRNAs are abnormally expressed in many types of diseases, including heart disease, inflammatory diseases, and especially cancers [20, 21, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-148-3p enhanced the migratory ability of SCs, while inhibition attenuated SC migration in vitro [43]. These effects occur in unison with other miRNAs such as miR-132, miR-210, miRNA sc-3, miR-221, and miR-222, which also increase the migratory ability of SCs, and miRNA sc-8, miR-9, miR-98, miR-1, and miR-182, which diminish this ability [45].…”
Section: Discussionmentioning
confidence: 99%